Student Worksheet Design Peration Material for Rank Shape and Root Shape to Develop Students' Comprehension Skills - Aslami Ode Hasim; Abdillah Abdillah (Lembaga Intelektual Muda Maluku, 2024)
The limited learning media, especially in studying the material of rank form and root form for students of SMA Negeri 4 Waesala motivated the author to make student worksheet practical, easy to understand, interesting, because it is equipped with pictures and systematics arranged in sequence with simple and clear language. This study aims to produce Student Worksheets on the operation material of binding shapes and root shapes of class X SMA Negeri 4 Waesala. The type of research used in the development process of student worksheet Mathematics operation material of rank form and root form is using the type of R&D (Research and Development) research, which is research that aims to produce a product and test the effectiveness of the product developed. The stages that researchers carry out in the development of student worksheet operation material for rank form and root form include analyzing the needs of student worksheet to be developed, developing initial products, expert validation and revision, small group trials, large group trials, final products. The subjects in this study totaled 27 people. Data collection techniques used observation, questionnaires, and interviews. The data analysis technique used is descriptive. Based on the results of data analysis, the student worksheet feasibility test was carried out through three stages as follows, namely the first stage of material validation tests, design, and language, the results of which all experts declared feasible. The second phase of the small group trial with 10 students, the result is that the student worksheet design is stated to be very interesting, but in terms of language it still needs to be simplified so that it is easier for students to understand. The third stage of the large group trial, the result is that the student worksheet design is suitable for use as a medium for learning mathematics, especially in the operation material of rank form and root form in grade X of SMA Negeri 4 Waesala. Most students stated that the design of student worksheet was interesting, as evidenced by 34 students who stated that they strongly agreed that the learning process was carried using student worksheet